An Analysis on Teaching English Strategies for Young Learner at SDN Mrican 1 Kediri - Ramadhani, Safira Putri (IREELL: Indonesian Review of English Education, Linguistics, and Literature, 2024)
Previously, English was only taught to secondary students, but now English is also taught to elementary school students. This is due to the increasing number of English language educators and the increasing development of curriculum and materials to deal with the question of how to teach EFL to young learner. This research aims to identify the problems faced by teachers in applies these strategies and analyze the teaching English strategies for young learners at SDN Mrican 1 Kediri. This research used qualitative descriptive. The instruments used for data collection were observation and interviews. The subject of the research is one of an English teacher at SDN Mrican 1. The research results of study, it is known that teachers use seven strategies out of nine strategies in Piller and Skillings (2005) theory in IV class. Those are demonstration, choral drill, look and say, read and say, pictorial illustration, verbal illustration, and questioning. The researcher also found five problems faced by teacher in teaching English for young learner ;1) insufficient facilities, (2) students pay less attention to the teacher, (3) students lack of motivation, and (4) students pronunciation are not clear, and (5) students cannot understand the material.